2017
DOI: 10.1186/s12864-017-3885-1
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome of a “sleeping” invader: de novo assembly and annotation of the transcriptome of aestivating Cornu aspersum

Abstract: Background Cornu aspersum is a quite intriguing species from the point of view of ecology and evolution and its potential use in medical and environmental applications. It is a species of economic importance since it is farmed and used for culinary purposes. However, the genomic tools that would allow a thorough insight into the ecology, evolution, nutritional and medical properties of this highly adaptable organism, are missing. In this work, using next-generation sequencing (NGS) techniques we assessed a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…Our transcriptome assembly had the vast majority of all reads mapping back to the assembly, and 100% of the mapped fragments were found mapped as proper pairs (yielding concordant alignments 1 or more times to the reconstructed transcriptome). Furthermore, our findings are superior to Parmakelis et al [57], Diray-Arce et al [58], and Khudyakov et al [59] who found that 65.58%, 72.91%, and 86.60% of the total raw reads could be mapped back to the assembly. This high concordance in our transcriptome might be due to the K-mer which was set at the maximal value of 32-mer [60].…”
Section: Discussioncontrasting
confidence: 80%
“…Our transcriptome assembly had the vast majority of all reads mapping back to the assembly, and 100% of the mapped fragments were found mapped as proper pairs (yielding concordant alignments 1 or more times to the reconstructed transcriptome). Furthermore, our findings are superior to Parmakelis et al [57], Diray-Arce et al [58], and Khudyakov et al [59] who found that 65.58%, 72.91%, and 86.60% of the total raw reads could be mapped back to the assembly. This high concordance in our transcriptome might be due to the K-mer which was set at the maximal value of 32-mer [60].…”
Section: Discussioncontrasting
confidence: 80%
“…As it can be easily assumed, given the vast amount of data produced by NGS, developing a massive data storage and management solution and creating bioinformatic tools to effectively analyze it will be the most crucial step for the successful application of NGS methodology (72). The full benefit of NGS will not be achieved until bioinformatics are able to maximally utilize and interpret these enormous short-read sequences into molecular and genetic useful information (73).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the databases including annotated ncRNA transcripts [e.g., miRBase (5), lncRNAdb (6), NONCODE (7) etc.] are expanding constantly with novel sequences, mainly due to the technological advancement through the establishment of high-throughput next-generation (NGS) technologies (8,9). In particular, NGS has revealed many ncRNAs originating from protein-coding genes (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%